(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Any branch of science has significant works and important inferences which have not lost their actuality up to now and show the ways to study and understand the meaning of object and phenomenon. The article analyzes the current scientific concepts of grammar of the Kazakh language, which are found in the works of Kazakh scientists in the early twentieth century. The inferences related to the use of the language make the foundation of functional direction, and the first symbols of it are shown in the research works of A. Baitursynuly, K. Zhubanov, S. Amanzholov. These scholars did not only establish the foundation of Kazakh linguistics but also defined the scientific directions in linguistics. One of these directions in the language is a functional direction. This article looks at the works of A. Baitursynuly and K. Zhubanov related to the category of verbs and S. Amanzholov’s works related to the category of case.